The existential paradox between code and conduct: Decoupling and its far reaching consequences in higher Education - M Ali Hamza; Alia Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
There is no dearth of rules, policies and codes in Higher Education Institutions (HEIs) of Pakistan, but of conduct. This decoupling of code and conduct and its consequences have mostly been studied at organizational level in non-academic settings. This paper extends the understanding of decoupling by studying its far reaching effects on individuals (employees; faculty and staff) in HEIs' of Pakistan. Data analyses from a survey of 215 respondents from nine public universities of Lahore, Pakistan, reveal that decoupling seeds negative perceptions among employees toward the legitimacy of institutions' efforts for ethics program and sources unethical behavior. This wave moves on and causes an increase in cynicism and psychological contract breach among employees, which ultimately exhaust them emotionally. Beside practical implications of the study in higher education, paper also provides theoretical contribution by offering a formula to calculate decoupling. Paper also provides limitations and guidelines for future study.
Keywords: 330; Decoupling; Internal Legitimacy; Psychological Contract Breach; Cynicism; Emotional Exhaustion